Rejang Pedawa dance as a medium for ethnopedagogical-based adolescent learning - Ardiyani, Luh Putu Cita; Pitriani, Komang; Jero, Ni Wayan Jemiwi (Dharmakirti : International Journal of Religion, Mind and Science, 2025)
Background: The ethno-pedagogical-based educational approach serves as a medium for the socialization of cultural values, as it contains local content that assists individuals in their social lives. Ethnopedagogical education becomes a variant of the learning process that is conducted by studying local arts in each region. One of these local arts is the Rejang Dance of Pedawa Village. This dance contains cultural values that can provide behavioral orientation to the people of Pedawa Village, especially young women. This research aims to analyze the existence of the Rejang Dance of Pedawa Village as an ethno-pedagogical basis that can be optimized in developing the character of young women. Methods: Research on the Rejang Dance of Pedawa Village as a medium for developing adolescent character based on ethno-pedagogy using a qualitative approach. The data analysis techniques from this research consist of data collection, data reduction, data presentation, and conclusions. This research uses a data collection process consisting of interviews, observations, and document studies. Findings: Dance is considered to develop social, emotional, and cognitive intelligence. Learning dance can serve as a medium for improving social intelligence because its teaching emphasizes interaction within learning groups. The desire to continue learning will also shape the character of "self-regulation," where individuals can control themselves and evaluate themselves. The actions and solutions created are not merely formalities but hold significance. Through non-formal educational institutions (traditional villages), character-building youth have the responsible freedom to take all kinds of actions, that are oriented towards the public. Action becomes an embodiment, that students as learners have a contextual orientation, what is obtained is not only enjoyed theoretically but also implemented practically. This is the habitus and utility of education in building students' character in the dimension of "cultural capital." Conclusion: On the other hand, the existence of art attraction can also be used to improve character values for teenage girls. Novelty/Originality of this article: In Ethno pedagogy, the Rejang Dance of Pedawa Village can be seen as an opportunity to instill character and emotional values by integrating traditional elements into character-based learning elements.